The Effect of Shrimp Waste Hydrolysate on Broiler’s Tibia Weight, Calcium and Phosphorous Content - Mahata, Maria Endo (Pakistan Journal of Nutrition, 2012)
An experiment was conducted with 80 unsexed broilers of Arbor Acress CP 707 strain to determine the effect of shrimp waste hydrolysate on tibia bone weight, calcium and phosphorus content. This study involved a Completely Randomized Design (CRD) with 4 treatments (0, 4, 8 and 12% of shrimp waste hydrolysate) and 5 replicates for each treatment. Diets were isonitrogenous (22% of crude protein) and isocaloric (2900 kcal/kg diet). Measured variables were weight of tibia bone, calcium and phosphorus content of tibia bone. Data were analyzed by analysis of variance for CRD. Result shown that increasing of shrimp waste hydrolysate levels in diet had no effect (p>0.05) on tibia bone weight and calcium content, but decreasing of phosphorous content (p